Unveiling gender differences: the impact of technostress on student satisfaction in online learning environments - Nurul Nadia Abd Aziz,; Indarawati Tarmuji,; Shamsinar Rahman,; Siti Fahazarina Hazudin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research investigates the moderating role of gender in the association between techno stress and student satisfaction in the context of online learning. Despite the benefits that are offered by the advances of ICT, difficulties in adapting to and excessive use of technology can lead to techno stress and impact the well-being of university students and their learning environment. Employing a quantitative approach, the questionnaires were distributed to the students at Universiti Teknologi MARA (UiTM), resulting in 234 valid responses. The research employs a comprehensive framework encompassing four key predictors: technooverload, techno-complexity, techno-insecurity, and techno-uncertainty. Utilising Structural Equation Modeling (SEM) through AMOS 27.0, the study reveals a significant negative correlation between technostress and student satisfaction, emphasising the impact of technology on the overall learning experience. Notably, female students show a heightened vulnerability to technostress-induced dissatisfaction compared to males, highlighting the need for diverse perspectives in designing online learning environments. The study underscores the importance of user-centric design in creating a conducive online learning environment. Focusing on user-friendly interfaces and continuous technology integration can mitigate student stress, enhancing satisfaction. This research contributes a validated technostress model for exploring its nuanced effects on student satisfaction. Importantly, this study highlights that these effects can differ significantly for male and female students. Educational institutions and policymakers stand to gain valuable insights from this research, enabling them to optimise online learning environments in a manner that caters to the diverse needs of all students.